GRP-030 Audit of Pharmacists' Interventions When Screening Adult Chemotherapy Prescriptions on an Electronic Prescribing System. (12th March 2013) - Stoner, N; Dhaliwal, S; Langran, C; Chan, E
Abstract : Background: The UK Cancer Standards require there to be protocols for chemotherapy treatment. The Thames Valley Cancer Network (TVCN) has developed and maintained network-wide protocols, which are continually updated for each tumour site-specific group. Clinical verification of chemotherapy prescriptions by pharmacists is an essential step to ensure patient safety and compliance with protocols, in line with national standards. Purpose: To audit pharmacists' interventions when clinically screening adult chemotherapy, clinical trial and supportive care prescriptions for oncology and haematology patients in the Oxford University Hospitals NHS Trust (OUH), and to ascertain the level of compliance of these prescriptions with relevant protocols and guidelines. To compare results with the audit undertaken in OUH in 2010. Materials and Methods: Pharmacists clinically screening the prescriptions completed an intervention form at the time of screening to enable prospective data collection over a three-week period. The screening pharmacists graded the intervention at the time of data collection, and interventions were subsequently independently graded by the investigator. The results of this audit are compared to a previous audit carried out for OUH, and the aim was to compare interventions during the two audit years. Results: The OUH had a decrease in the number of interventions made by 24% compared to the audit in 2010. The number of moderate and major interventions made also decreased by 5% and 23% respectively. Time spent on making interventions also decreased. Incorrect frequency/duration/date of treatment, inappropriate dose, confirmation of dose/regimen/prescriptions were prescribed according to guidelines compared to just 68% in 2010. Conclusions: The changes implemented after the OUH audit in 2010 were successful and this is seen in the results. To improve further this audit should be conducted across TVCN hospitals every year so that each hospital can monitor their progress. Having regular training days for clinicians would be beneficial. No conflict of interest.